Relationship between Vitamin D AND IL6 in Convalescent Healthcare Workers with Covid-19 in Baquba Hospitals in Diyala Province - Maysam Abbas; Luma T. Ahmed; Mohammed A. Alkarkhi (Institute of Medico-legal Publications Pvt Ltd, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) and pandemic, caused by severe acute respiratorysyndrome coronavirus 2 (SARS-CoV-2), has become a major concern globally. One hundred ConvalescentHCWs patients with COVID-19 works in Diyala, Hospitals center, from October 2020 to March 2021 wereincluded. We recruited 100 non-infected from healthy people and 100 PCR-confirmed infected HCWs. In thisreview, we have summarized and discussed recent immunological studies focusing on the response of the hostimmune system, cytokine storms such as IL6 have been discussed as part of immunopathology mechanismsin SARS-CoV-2 infection. This may help us understand patients’ immune status with COVID-19, particularlythose with severe clinical presentation, and form a basis for further immunotherapeutic investigations. Thisstudy calculate that there is the relation between IL6 and Vitamin D3 in convalescent patients, accountingfor a range of previously described clinical predictors and, potentially directing future therapeutic strategies,including about Vitamin D.